You are mine - Lucado, Max; Martinez, Sergio, 1937- (New York : Scholastic, 2002)
When Punchinello tries to prove his worth by getting more boxes and balls than the other Wemmicks, he learns that his maker, Eli, loves him because of who he is and not what he possesses
"This edition is only available for distribution through the school market"--P. [4] of cover
Keywords: Conduct of life -- Juvenile fiction; Self-acceptance -- Juvenile fiction